Angka Kejadian Gangguan Cemas dan Insomnia pada Lansia di Panti Sosial Tresna Werdha Wana Seraya Denpasar Bali Tahun 2013 - Aninda Vikhanti, I Dewa Ayu; Indah Ardani, I Gusti Ayu (E-Jurnal Medika Udayana; Vol 6 No 10 (2017): E-Jurnal Medika Udayana, 2017)
Stress and changes that accompany aging can be an aggravate factor of anxiety disorder. Anxiety disorder can occur together with sleep disorder. It is difficult to determine whether anxiety disorders cause sleep disorders, or sleep disorder cause anxiety. The concern is that prolonged anxiety disorders, more than six months, can worsen if left untreated. This study is to determine the number of elderly who experience anxiety disorders and insomnia, as well as their relationship, in Social Institutions Tresna Werdha Wana Seraya. This study used a non-experimental, cross sectional. These samples included 15 people. The research instrument used in this study is the Hamilton Anxiety Rating Scale and Insomnia Screening. As the result, in the age group of 60-70 years there is one person who had the anxiety disorders (16.6%), two people who have insomnia (33.3%) and 1 person experiencing anxiety disorders and insomnia (16.6%). In the age group 71-80 years, there are 2 people who experience anxiety disorders (22.2%), two people experience insomnia (22.2%), and two people experience anxiety disorders and insomnia (22.2%). In the group of female sex, there are 3 people experiencing anxiety disorders (27.2%), three people experience insomnia (27.2%), and three people have anxiety disorders and insomnia (27.2%). In the male gender 1 person experiencing insomnia and no experience anxiety disorders. There are various factors that influence the occurrence of anxiety disorders and insomnia in the elderly, the age and gender. Anxiety disorders tend to occur at a younger age and female gender.